Modelling optimal vaccination strategies against COVID-19 in a context of Gamma variant predominance in Brazil - Ferreira, Leonardo Souto [UNESP]; de Almeida, Gabriel Berg [UNESP]; Borges, Marcelo Eduardo; Simon, Lorena Mendes; Poloni, Silas [UNESP]; Bagattini, Ângela Maria; da Rosa, Michelle Quarti Machado; Diniz Filho, José Alexandre Felizola; Kuchenbecker, Ricardo de Souza; Camey, Suzi Alves; Kraenkel, Roberto André [UNESP]; Coutinho, Renato Mendes; et al. (Elsevier, 2022)
Introduction: Brazil experienced moments of collapse in its health system throughout 2021, driven by the emergence of variants of concern (VOC) combined with an inefficient initial vaccination strategy against Covid-19. Objectives: To support decision-makers in formulating COVID-19 immunization policy in the context of limited vaccine availability and evolving variants over time, we evaluate optimal strategies for Covid-19 vaccination in Brazil in 2021, when vaccination was rolled out during Gamma variant predominance. Methods: Using a discrete-time epidemic model we estimate Covid-19 deaths averted, considering the currently Covid-19 vaccine products and doses available in Brazil; vaccine coverage by target population; and vaccine effectiveness estimates. We evaluated a 5-month time horizon, from early August to the end of December 2021. Optimal vaccination strategies compared the outcomes in terms of averted deaths when varying dose intervals from 8 to 12 weeks, and choosing the minimum coverage levels per age group required prior to expanding vaccination to younger target populations. We also estimated dose availability required over time to allow the implementation of optimal strategies. Results: To maximize the number of averted deaths, vaccine coverage of at least 80 % should be reached in older age groups before starting vaccination into subsequent younger age groups. When evaluating varying dose intervals for AZD1222, reducing the dose interval from 12 to 8 weeks for the primary schedule would result in fewer COVID-19 deaths, but this can only be implemented if accompanied by an increase in vaccine supply of at least 50 % over the coming six-months in Brazil. Conclusion: Covid-19 immunization strategies should be tailored to local vaccine product availability and supply over time, circulating variants of concern, and vaccine coverage in target population groups. Modelling can provide valuable and timely evidence to support the implementation of vaccination strategies considering the local context, yet following international and regional technical evidence-based guidance.
Keywords: COVID-19; Immunization; Modelling; Vaccines